Carmustine induces platelet apoptosis. (July 2015) - Zhang, Jie; Chen, Mengxing; Zhang, Yiwen; Zhao, Lili; Yan, Rong; Dai, Kesheng
Abstract Carmustine is one of the alkylating chemotherapeutic agents, which are used to treat various types of cancers, such as brain tumors, Hodgkins and non-Hodgkins lymphoma and multiple myeloma. However, carmustine has the side effect of thrombocytopenia, and the mechanism is not completely understood. In this study, we show that carmustine dose-dependently induced depolarization of mitochondrial inner transmembrane potential (ΔΨm), up-regulation of Bax, down-regulation of Bcl-2 and caspase-3 activation. Carmustine did not induce surface expression of P-selectin or PAC-1 binding, whereas, obviously reduced collagen and thrombin-induced platelet aggregation. Dicumarol, c-Jun NH2-terminal kinase-specific inhibitor, reduced carmustine-induced ΔΨm depolarization in platelets. The numbers of circulating platelets were reduced, and the tail bleeding time was significantly increased in mice that were injected with carmustine. Taken together, these data indicate that carmustine induced platelet apoptosis, suggesting the possible pathogenesis of thrombocytopenia in patients treated with carmustine.